Energy (in)security: world‐making in an age of scarcity. Issue 4 (26th November 2014) - Bridge, Gavin
Abstract : 'Energy security' has quickly assumed a significant place in the lexicon of policy. Like other handy couplets for characterising socio‐natural relations (such as carrying capacity and resource scarcity), energy security is a powerful framing device: it constructs worlds, normalises certain practices of resource use, and establishes grounds for intervention. In this paper, I explore some of the different ways in which energy (in)security is now being used, and reflect on the political work it currently performs. I highlight the historical conditions under which energy and security have become combined, the close association of energy security with crude oil imports, and the imprint that oil has left on the concept. Although geography has tended to interpret practices of security through either a territorial or biopolitical perspective, in this paper I consider how energy's securitisation proceeds through a set of imaginative and calculative practices (referred to here as 'geo‐metrics'). I use the language of 'world‐making' to draw attention to the techno‐political practices associated with securitising energy, and their capacity for constituting political ecological relations. I illustrate this with reference to a growing body of knowledge and expertise in the calculation and design of energy security indicators.